Diabetic Nephropathy: Perspective on Extracellular Vesicles - Lu, Yanfang; Liu, Dongwei; Feng, Qi; Liu, Zhangsuo (Frontiers in Immunology, 2020)
Diabetic nephropathy (DN) is a major microvascular complication of diabetes mellitus. It is the most frequent cause of end-stage renal disease with no definitive therapy available so far. Extracellular vesicles (EVs), including exosomes, microvesicles, and apoptotic bodies, are nano- and micron-sized heterogeneous vesicles that can be secreted by almost all cell types. Importantly, EVs contain many biologically active materials, such as RNAs, DNAs, proteins, and lipids, from their parental cells, which can be transported to their recipient cells to mediate intercellular communication and signaling. Accumulating studies demonstrated that EVs, mainly exosomes and microvesicles, participated in the pathophysiological process of DN. Recently emerging studies also found that the contents of EVs in the urine (miRNAs, mRNAs, and proteins) could be used as potential biomarkers for DN. Therefore, in this mini review, the generation, isolation methods, and biological function of EVs were introduced and then the current information about the mechanism and diagnostic value in the development of DN was summarized. Moreover, the review also discussed the future challenges of exploring the role of EVs in kidney disease.